Guided endodontics: Management of calcified tooth with a large periapical lesion using cone beam computed tomography and three-dimensional printed guide: A case report - Anciya Mohamed Nazar; Liza George; Josey Mathew (Wolters Kluwer Medknow Publications, 2022)
The aim of this case report is to depict novel guided endodontic approach for the management of calcified tooth with a large periapical lesion using cone beam computed tomography (CBCT) and three-dimensional (3D) printed guide. The patient presented with swelling on the upper left front tooth region. Intraoral periapical radiograph revealed periapical radiolucency associated with upper left lateral incisor. Due to pulp canal calcification, location of the root canal was judged to be difficult and associated with a high risk of perforation. A CBCT and an intraoral surface scan were performed and matched using software for virtual planning of guided endodontics. After planning the position of the drill for root canal location, a virtual template was designed and 3D printed which was then used for guided endodontic access.